Diversifying High Schools in Racially Changing Suburban Districts: Expanding Opportunity, Creating Barriers?. (26th May 2016) - Frankenberg, Erica; Ayscue, Jennifer B.; Tyler, Alison C.
Abstract : Although demographic change is happening more rapidly at the elementary school level, the intersection of these demographic trends with the changing mission of high schools may offer the opportunity to reduce some of the persistent racial gaps in educational attainment. At the same time, when schools became diverse as desegregation took place, stratification within schools occurred, leading to inequality within diverse schools. Thus, this article seeks to examine whether high schools can help to expand opportunity for low-income students and students of color as suburban racial change occurs. To answer this question, this article draws on school-level interviews in six public high schools in racially changing suburban districts in some of the nation's largest metropolitan areas. High schools in this study focused on ways to provide access to diverse students through structural reforms and information dissemination, yet they also saw academic programs as a way to compete for certain students to shape their student body composition and maintain enrollment.